Storage of cardiac glycosides in vacuoles of Digitalis lanata mesophyll cells - Hoelz, Hubert; Kreis, Wolfgang; Haug, Birgit; Reinhard, Ernst (Phytochemistry, 1992)
The intracellular distribution of cardenolides in mesophyll cells of Digitalis lanata was investigated. Plantlets were grown under axenic conditions. Protoplasts were isolated from sliced leaves and lysed to yield intact vacuoles which were subsequently purified by flotation centrifugation. The cardenolide contents of mesophyll cells, protoplasts and vacuoles were analysed by HPLC. Primary glycosides, e.g. the lanatosides A and C, were found to be stored exclusively in the vacuoles. Although present in quite high amounts in leaf tissue, secondary glycosides, such as α-acetyldigoxin or α-acetyldigitoxin, could not be detected in vacuoles isolated from mesophyll cells. It is concluded that in Digitalis leaves cardenolides are stored solely as primary glycosides, whereas secondary glycosides found in leaf extracts are either biosynthetic intermediates or degradation products. © 1992.
UnivIS-Import:2015-03-05:Pub.1992.nat.dbio.LPB.storag
Keywords: cardiac glycosides; compartmentalization; Digitalis lanata; protoplasts; Scrophulariaceae; vacuoles